STATUS OF CENTRAL AND PERIPHERAL HEMODYNAMICS IN ADOLESCENTS WITH ESSENTIAL HYPERTENSION - I.V. Plotnikova; A.A. Sokolov; I.A. Kovalev; I.V. Trushkina; G.P. Filippov ("Paediatrician" Publishers LLC, 2008)
This work focuses on characteristics of central and peripheral hemodinamics and its correlation with 24 hours' profile of blood pressure and humoral status in adolescents with primary arterial hypertension. 91 adolescent was examined, 27 patients had phenomenon of white coat hypertension, other patients had labile (n = 37) and stable (n = 27) arterial hypertension. Maximal value of myocardial mass of left ventricle was in adolescents with stable arterial hypertension. The signs of remodeling of myocardium of left ventricle were stated in 6 (6,5%) patients. the intensity of hypertrophy of left ventricle concerned with high variability of systolic blood pressure during daylight hours and its inadequate reduction during a night. Indices of central and peripheral hemodynamics in a number of cases associated with humoral factors - concentration of uric acid and willebrand factor in blood plasma.Key words: adolescents, arterial hypertension, heart remodeling, uric acid, willebrand factor.